Strategi PDM Kabupaten Sorong dalam Meningkatkan Mutu Pendidikan Lembaga Pendidikan Agama Islam di Daerah 3T - santoso, budi; Khasanah, Khasanah (Jurnal Pendidikan Agama Islam, 2023)
The quality of education in 3T areas (lagging, leading and outermost) cannot be equated with education in other areas. Because the 3T area needs to be given different treatment in order to catch up with the lag from other regions. This research discusses the strategy conducted by the Regional Leadership of Muhammadiyah Sorong Regency in improving the quality of education for Islamic educational institutions located in the 3T area. The method used in this study is a qualitatively discrete method with a type of field research that is direct researchers to the location of research to obtain concrete data that has to do with the problem to be discussed. The method used is descriptive-qualitative analysis, data sourced from in-depth interviews, observations and documentation, After the data collected will be analyzed with the analysis model Miles, Huberman and Saldana (2014) consisting of: condensation of data, presentation of data, and drawing conclusions. The scalpel used in this study using Sudarwan Danim's theory (2007:56) says that an institution wants to improve the quality of its education, so it must involve at least five dominant factors, namely: Leadership of the Principal, Teacher, Curriculum.